Ethnobotanical studies on some wild plants of head Qadirabad and adjoining areas, Pakistan - Uzma Hanif; Sadia Mushtaq; M Ajaib; Saiqa Ishtiaq; Shazia Khurshid; Mobina Ulfat (International Journal of Phytomedicine, 2013)
An Ethno botanical survey was carried out during 2011-2012 in order to document the importance of the plants in Qadirabad, Tehsile Phalia and District Mandi Bahauddin, Punjab, Pakistan. A total of 54 plants were collected belonging to 29 families, from which 50 were dicots and 4 were monocots, 28 families were angiosperms and only 1 was Pteridophyte. Papilionaceae was the dominant family. The plant species collected from the studied area and were identified with flora of Pakistan. Plants were categorized in single usage plants, two usage plants, and multi usage plants. It was observed that mostly plants were used for treatment of different kinds of diseases like stomachic diseases, Piles, constipation; bleeding wounds, snake bite etc. Cutting of trees for earning livelihood were common. It was also observed during this study, that harvesting of the plants is very common for local uses